Paths to Faith: Religious Conversion among Filipino Expatriates in the UAE - Tariq, Maimoona Amir; Klominek, Johannes (Advances in Social Sciences Research Journal, 2026)
Research on conversion to Islam has largely focused on Western Muslim-minority contexts, where converts often encounter marginalization and contested belonging. This study addresses a significant gap by examining conversion narratives among Filipino Christian expatriates in the United Arab Emirates (UAE), a Muslim-majority and multicultural setting where Islam is institutionally embedded in everyday life. Drawing on ten semi-structured interviews with adult Filipino converts, the research employs reflexive thematic analysis to explore motivations, relational influences, and identity negotiations shaping conversion processes. Findings indicate that conversion unfolded as a gradual and multi-layered process in which internal spiritual searching typically preceded social interaction. Digital daʿwah platforms emerged as cognitively active yet socially safe spaces for theological exploration. The study identifies the presence of an ambient Islamic infrastructure, including the public call to prayer, Ramadan’s transformation of social life, institutional support, and accessible religious education, which structurally facilitates religious encounter within expatriate experience. However, participants also reported experiences of marginalization within Muslim communities, challenging assumptions that conversion in Muslim-majority contexts is inherently less complex. The study contributes to theoretical discussions on religious conversion by highlighting the importance of socioreligious context in shaping contemporary spiritual transformation.